2019
DOI: 10.1139/apnm-2018-0638
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic responses to an exercise stress test in Parkinson’s disease patients without orthostatic hypotension

Abstract: The presence of postganglionic sympathetic denervation is well established in Parkinson’s disease (PD). Denervation at cardiac and blood vessel sites may lead to abnormal cardiovascular and hemodynamic responses to exercise. The aim of the present investigation was to examine how heart rate (HR) and hemodynamics are affected by an exercise test in PD patients without orthostatic hypotension. Thirty individuals without orthostatic hypotension, 14 individuals with PD, and 16 age-matched healthy controls performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…The literature indicates that both performance fatigability and perceived fatigability are often elevated in people with PD. Studies providing insight into fatigability during whole-body activities in people with PD are presented in Table 1 [29][30][31][32][33][34][35][36][37][38][39][40]. When compared to healthy controls, it is consistently reported that people with PD demonstrate reduced distance walked and lower cardiorespiratory fitness [29,30,33,35,38,39].…”
Section: Evidence Of Elevated Fatigability In Parkinson's Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…The literature indicates that both performance fatigability and perceived fatigability are often elevated in people with PD. Studies providing insight into fatigability during whole-body activities in people with PD are presented in Table 1 [29][30][31][32][33][34][35][36][37][38][39][40]. When compared to healthy controls, it is consistently reported that people with PD demonstrate reduced distance walked and lower cardiorespiratory fitness [29,30,33,35,38,39].…”
Section: Evidence Of Elevated Fatigability In Parkinson's Diseasementioning
confidence: 99%
“…When compared to healthy controls, it is consistently reported that people with PD demonstrate reduced distance walked and lower cardiorespiratory fitness [29,30,33,35,38,39]. Multiple reports of reduced performance during less demanding exercise protocols in people with PD compared to healthy controls [31,37,40,41] suggest these individuals are likely predisposed towards increased fatigability during less strenuous activities as well. Elevated perceived fatigability often occurs concomitantly with increased performance fatigability in people with PD.…”
Section: Evidence Of Elevated Fatigability In Parkinson's Diseasementioning
confidence: 99%
See 3 more Smart Citations